Effects of secondary warm up following stretching - Pearce, A. J.; Kidgell, D. J.; Zois, J.; Carlson, J. S. (European Journal of Applied Physiology, 2009)
Evidence suggests that static stretching inhibits muscular power. However, research does not reflect practice whereby individuals follow up stretching with secondary activity. This study investigated muscular power following stretching, and after a second bout of activity. Participants (n = 13) completed 3 randomized testing sessions which included a 5 min warm-up, followed by a vertical jump (VJ) on a force platform; an intervention (static stretching, dynamic, or control), followed by a second VJ. Participants then completed a series of movements, followed by a VJ, up to 60 min post activity. Immediately following the intervention, there was a 10.7% difference in VJ between static and dynamic stretching. The second warm up bout increased VJ height following the dynamic intervention, whereas the static stretching condition did not show any differences. The novel finding from this study demonstrates a second exercise bout does not reverse the effects of static stretching and is still detrimental to VJ.